'All good stories': historical fiction in pedagogy, theory, and scholarship. Issue 1 (2nd January 2019) - Hower, Jessica S.
Abstract: Academics have long had a fraught, complex relationship with popular culture, frequently scoffing at, dismissing, or chiding producers and consumers for their choices to sanitize, exoticize, or romanticize the past in print, theater, and film. From the literary perspective, the relationship is no less acrimonious. Yet despite discomfort on both sides, fictional forms of history exert a powerful, even inexorable influence – especially on students, who may find their way into history classes because of dramas like The Tudors, complete with all of the baggage that such series carry. Drawing extensively on historiographical turns from positivism through postmodernism as well as my own experiences teaching at a small liberal arts college and conducting scholarly research on the afterlives of the Tudor dynasty, I argue that historical fiction – broadly defined – has a crucial, tripartite role to play in the pursuit of history: as a pedagogical tool by which to help students grasp the theory and practice of history, as a theoretical framework by which to reconsider the relationship between history and fiction, and as a source base and form by which to enlarge the field of traditional academic history.